A Handlist of Illustrated Early Solomonic Manuscripts in German Public Collections - Dege-Müller, Sophia; Gnisci, Jacopo; Pisani, Vitagrazia (Aethiopica, 2022)
Illustrated manuscripts in the Ethiopic language, as material objects that carry textual and visual information, are among the most valuable sources of data for art historians specializing in this area. This article provides a handlist of illustrated early Solomonic manuscripts housed in German libraries and museums. The contribution was created within the framework of the AHRC-DFG project Demarginalizing medieval Africa: Images, texts, and identity in early Solomonic Ethiopia (1270–1527) so our data reflects the project’s research focus on visual matter. This is the first time that the illuminations of the manuscripts included in the handlist are analysed comprehensively. We believe that the resulting work sheds new light on the history of book illustration in early Solomonic Ethiopia and hope that it will provide researchers with a valuable instrument to foster comparative research and a more integrative approach to the study of Ethiopian art.